Policy statements of President Fidel V. Ramos - Ramos, Fidel Valdez 1928- ([Manila] Office of Press Secretary, Bureau of Communications Services, 1992)
Monthly.
Description based on: no. 10, May 1993 issue.
Keywords: Philippines. -- President (1992-1998 : Ramos); Philippines -- Economic conditions -- 1992-1998.; Philippines -- Economic policy -- 1992-1998.; Philippines -- Foreign relations -- 1992-1998.; Philippines -- Politics and government -- 1992-1998.